Black–White Difference in the Impact of Long-Term Blood Pressure From Childhood on Adult Renal Function: The Bogalusa Heart Study - Yan, Yinkun (Am J Hypertens, 2018)
BACKGROUND: To examine racial difference in the impact of long-term burden of blood pressure (BP) from childhood on adult renal function between middle-aged blacks and whites. METHODS: The study cohort consisted of 1,646 whites and 866 blacks aged 20–51 years at follow-up who had BP measured at least 4 times since childhood, with a mean follow-up period of 25.3 years. The area under the curve (AUC) was calculated as a measure of long-term burden of BP from childhood to adulthood. Estimated glomerular filtration rate (eGFR) was calculated based on serum creatinine to assess renal function in adulthood. RESULTS: Black vs. white adults had significantly higher values of eGFR and long-term burden of systolic BP for both males and females. In multivariable linear regression analyses, adjusting for sex, adult age, body mass index, smoking, and alcohol use, adult eGFR was significantly and negatively associated with adult systolic BP (standardized regression coefficient [β] = −0.10, P = 0.005) and diastolic BP (β = −0.11, P = 0.003) in blacks, but not in whites. The total BP AUC values were also significantly and negatively associated with adult eGFR (β = −0.10, P = 0.005 for systolic BP and β = −0.09, P = 0.013 for diastolic BP) in blacks only. Childhood BP was not significantly associated with adult eGFR in blacks and whites. CONCLUSIONS: These findings suggest that black–white disparities in the influence of elevated BP on the development of renal dysfunction occur in middle adulthood, which underscores the importance of BP control in the black population.